1994
DOI: 10.1111/j.1469-7998.1994.tb04869.x
|View full text |Cite
|
Sign up to set email alerts
|

Apodemus sylvaticus infected with Heligmosomoides polygyrus (Nematoda) in an arable ecosystem: epidemiology and effects of infection on the movements of male mice

Abstract: We studied the epidemiology of Heligmosomoides polygyrus (Nematodd) in the wood mouse (Apodemus sylvaticus) in an arable ecosystem, and investigated any association between infection and the movement patterns of male mice by manipulating worm burdens. Methods included the live‐trapping of mice, estimation of worm burdens by faecal analysis, administration of either an anthelminthic or water (as a control) and the radio‐tracking of selected animals. Heligmosomoides polygyrus showed an overdispersed distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 75 publications
(67 reference statements)
0
38
1
Order By: Relevance
“…Since data on small-mammal movements and sizes of home ranges are not consistent, such comparison are limited for A. agrarius and A. flavicollis in middle Europe, and suggest that home range size is variably influenced by habitat type, season, mouse age and sex (BabinskaWerka et al 1981, Horvath and Trocsanyi 1998, Vukicevic Radic et al 2006. Furthermore, Brown et al (1994) observed an association between parasite infection and movement parameters and home range of males in the wood mouse A. sylvaticus.…”
Section: Discussionmentioning
confidence: 97%
“…Since data on small-mammal movements and sizes of home ranges are not consistent, such comparison are limited for A. agrarius and A. flavicollis in middle Europe, and suggest that home range size is variably influenced by habitat type, season, mouse age and sex (BabinskaWerka et al 1981, Horvath and Trocsanyi 1998, Vukicevic Radic et al 2006. Furthermore, Brown et al (1994) observed an association between parasite infection and movement parameters and home range of males in the wood mouse A. sylvaticus.…”
Section: Discussionmentioning
confidence: 97%
“…The prevalence of H. polygyrus is frequently low in populations of C. glareolus (Lewis 1987) and correspondents to the results obtained in the present study. Brown et al (1994a) studied the epizootiology of H. polygyrus in a population of A. sylvaticus in England and proved an overdispersed distribution of the nematode, with higher prevalence of infestation in males and heavier rodents. The prevalence of infestation was highest in spring and declined in autumn, and infected rodents moved more often and faster than uninfected rodents (Brown et al 1994b).…”
Section: Discussionmentioning
confidence: 99%
“…The seasonal variation of H. polygyrus intensity and also, to some extent, the inter-annual variation may be related to very dry conditions during summer which do not favor free-living larval stage survival and therefore transmission. Previous studies have also described the seasonal character of prevalences (Brown et al 1994) and abundances (O'Sullivan et al 1984, Abu-Madi et al 1998) of H. polygyrus in wood mice. In the present study, seasonal differences indicate that higher burdens occurred during spring, which characteristically constitutes the lowest point of the wood mouse's annual population cycle.…”
Section: Discussionmentioning
confidence: 99%